2023
DOI: 10.1007/s40544-022-0710-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface-functionalized design of blood-contacting biomaterials for preventing coagulation and promoting hemostasis

Abstract: The anticoagulation and hemostatic properties of blood-contacting materials are opposite lines of research, but their realization mechanisms are inspired by each other. Contact between blood and implantable biomaterials is a classic problem in tribological research, as both antithrombotic and hemostatic materials are closely associated with this problem. Thrombus formation on the surfaces of blood-contacting biomedical devices can detrimentally affect their performance and patient life, so specific surface fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(43 citation statements)
references
References 147 publications
0
43
0
Order By: Relevance
“…This analysis places great importance on the identification of exceptional systems, which are characterized by low stabilization energy, longer wavelengths, and higher oscillator strengths. 54,55 These parameters as the basis for assessing the reactivity of the particles, guided by the fundamental energy–frequency relationship, were analyzed and expressed using eqn (1): E = hf Here, E represents the energy of the particle, h is the Planck constant ( h = 6.626 × 10 −34 J s), and f denotes the frequency of the particle. As per this formula, it is evident that energy is directly proportional to frequency.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis places great importance on the identification of exceptional systems, which are characterized by low stabilization energy, longer wavelengths, and higher oscillator strengths. 54,55 These parameters as the basis for assessing the reactivity of the particles, guided by the fundamental energy–frequency relationship, were analyzed and expressed using eqn (1): E = hf Here, E represents the energy of the particle, h is the Planck constant ( h = 6.626 × 10 −34 J s), and f denotes the frequency of the particle. As per this formula, it is evident that energy is directly proportional to frequency.…”
Section: Resultsmentioning
confidence: 99%
“…[54][55] It is pertinent to note that more often than not, the types of interaction encountered in a typical QTAIM analysis basically range from covalent bonding to partial covalent bonding and non-covalent bonding with the criteria for desirability being the ability to have an efficient in vivo desorption time especially for a drug delivery system as this hence as equally confirmed by several independent studies, the lesser the covalent nature of the interaction the greater the preference for an efficient drug delivery. [56][57][58][59][60] The r 2 1(r) and H(r) values show that firstly, the three BCP considered for Acetaminophen_COF tend towards partial covalent interaction, a trend which is equally obvious in Arsenic trioxide_COF, MERCAPTOPURINE_COF and Tioguanine_COF. Secondly, the first bond critical point for Clodronic acid_COF corresponding to the Cl 103 À H 52 is aberrant as it lacks both r 2 1(r) and H(r) (= 0 in both cases).…”
Section: Analysis Of the Quantum Theory Of Atom In Molecules (Qtaim)mentioning
confidence: 99%
“…The initiation of coagulation reactions that lead to blood clotting is an important issue in the use of nanoparticles (Wang et al, 2023). Berckmans et al showed that by improved blood collection and plasma preparation methods, exosomes are non‐coagulant and no relationship is present between the plasma concentrations of exosomes and coagulation factors (Berckmans et al, 2019).…”
Section: Considerations In the Use Of Exosomesmentioning
confidence: 99%